High-efficiency nonlinear frequency conversion enabled by optimizing the ferroelectric domain structure in x-cut LNOI ridge waveguide - Su Yawen; Zhang Xinyu; Chen Haiwei; Li Shifeng; Ma Jianan; Li Wei; Niu Yunfei; Qin Qi; Yang Shaoguang; Deng Yu; Zhang Yong; Hu Xiaopeng; et al. (Nanophotonics)
Photonic devices based on ferroelectric domain engineering in thin film lithium niobate are key components for both classical and quantum information processing. Periodic poling of ridge waveguide can avoid the selective etching effect of lithium niobate, however, the fabrication of high-quality ferroelectric domain is still a challenge. In this work, we optimized the applied electric field distribution, and rectangular inverted domain structure was obtained in the ridge waveguide which is beneficial for efficient nonlinear frequency conversions. Second harmonic confocal microscope, piezoresponse force microscopy, and chemical selective etching were used to characterize the inverted domain in the ridge waveguide. In addition, the performance of nonlinear frequency conversion of the periodically poled nano-waveguide was investigated through second harmonic generation, and the normalized conversion efficiency was measured to be 1,720 % W−1 cm−2, which is close to 60 % that of the theoretical value. The fabrication technique described in this work will pave the way for the development of high-efficiency, low-loss lithium niobate nonlinear photonic devices.